A deep one-class classifier for network anomaly detection using autoencoders and one-class support vector machines - Bountzis, Polyzois; Kavallieros, Dimitris; Tsikrika, Theodora; Vrochidis, Stefanos; Kompatsiaris, Ioannis (Frontiers in Computer Science, 2025)
IntroductionThe integration of deep learning models into Network Intrusion Detection Systems (NIDS) has shown promising advancements in distinguishing normal network traffic from cyber-attacks due to their capability to learn complex non-linear patterns. These approaches typically rely on both benign and malicious network traffic during training. However, in many organizations, collecting malicious traffic is challenging due to privacy restrictions, high costs of manual labeling, and requirement for advanced security expertise.MethodsIn this study, we introduce a deep one-class classification model that is trained exclusively on flow-based benign network traffic data, with the goal of identifying attacks during inference. The proposed anomaly detection model consists of two steps, a One-Class Support Vector Machine (OC-SVM) and a deep AutoEncoder (AE). While autoencoders have shown great potential in anomaly detection, their effectiveness can be undermined by spurious network activity located on the boundaries of their discriminating capabilities, thus failing to identify malicious behavior. Our model leverages the topological structure of the OC-SVM to generate decision scores for each traffic flow, which are subsequently incorporated into an autoencoder as part of the input feature space.ResultsThis approach enhances the ability of the autoencoder to detect incidents that deviate from normal patterns. Furthermore, we propose a heuristic method for tuning the trade-off parameter of the OC-SVM, based only on one-class data, achieving comparable performance to grid-based methods that require both benign and malicious labeled data. Experimental results on a benchmark network intrusion data set, the UNSW-NB15, suggest that OCSVM-AE performs well on unseen attacks and is more effective than traditional and deep-learning based one-class classifiers.DiscussionThe method makes no specific assumptions about the data distribution, making it broadly applicable and suitable as a complementary tool to signature-based intrusion detection systems.